2014
DOI: 10.1088/1367-2630/16/6/063038
|View full text |Cite
|
Sign up to set email alerts
|

Fast decoders for qudit topological codes

Abstract: Qudit toric codes are a natural higher-dimensional generalization of the wellstudied qubit toric code. However, standard methods for error correction of the qubit toric code are not applicable to them. Novel decoders are needed. In this paper we introduce two renormalization group decoders for qudit codes and analyse their error correction thresholds and efficiency. The first decoder is a generalization of a 'hard-decisions' decoder due to Bravyi and Haah (arXiv:1112.3252). We modify this decoder to overcome … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(98 citation statements)
references
References 65 publications
3
94
0
1
Order By: Relevance
“…The plot shows that the threshold achieved by the decoder increases monotonically with increasing qudit dimension, but quickly saturates to a maximum value of p (7919) th = 0.042 ± 0.09. Previous work performed on the noiseless syndrome measurement version of the HDRG in [15] suggests that this saturation is due to a syndrome percolation effect.…”
Section: Duclos-cianci and Poulin Achieves A Threshold Of Pmentioning
confidence: 91%
See 1 more Smart Citation
“…The plot shows that the threshold achieved by the decoder increases monotonically with increasing qudit dimension, but quickly saturates to a maximum value of p (7919) th = 0.042 ± 0.09. Previous work performed on the noiseless syndrome measurement version of the HDRG in [15] suggests that this saturation is due to a syndrome percolation effect.…”
Section: Duclos-cianci and Poulin Achieves A Threshold Of Pmentioning
confidence: 91%
“…The plot shows that the threshold achieved by the decoder increases monotonically with increasing qudit dimension, but quickly saturates to a maximum value of p (7919) th = 0.042 ± 0.09. Previous work performed on the noiseless syndrome measurement version of the HDRG in [15] suggests that this saturation is due to a syndrome percolation effect.In order to verify this hypothesis, we performed a simulation of the syndrome percolation threshold. This was done by generating the qudit noise and noisy syndrome measurements for each qudit dimension in the same way as for the decoder simulation.…”
mentioning
confidence: 91%
“…To prove Theorem 1, we show that gates of the form of Eq. (8) are transversal in all m orthogonal codes for polynomial degree r = m. To prove Theorem 2 we also prove that gates of the form in Eq. (7) are transversal in 3 -orthogonal codes.…”
Section: Transversal Operatorsmentioning
confidence: 94%
“…However, in the case of surface codes, it has been shown that some proposed renormalization-group (RG) algorithms can be generalized to qudit codes in a straightforward manner [8,51]. Moreover, recent work for the 3D fault-tolerant implementation of the qudit surface code using a hard-decision RG decoder [9] suggests that adaptations of such algorithms for higher spatial dimensions should be possible, however, the error correction thresholds would likely be degraded as the spatial dimension increases due to the larger stabilizer generators.…”
Section: Error Detectionmentioning
confidence: 99%
See 1 more Smart Citation